THE EVOLUTION OF ENGLISH AS THE GLOBAL LANGUAGE: THE IMPACT OF THE INTERNET AND AMERICAN MEDIA («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
English, once a language confined to the British Isles, has now become the lingua franca of the world. How did this transformation occur, and what role did the Internet and American media play in this process? Let's delve into the fascinating journey of English becoming the global language.
Keywords: language, marginalization, historical factors, cultural influences.